2001
DOI: 10.1002/app.1178
|View full text |Cite
|
Sign up to set email alerts
|

Positron annihilation lifetime studies of gas sorption and desorption in polyethylene and poly[1‐(trimethylsilyl)‐1‐propyne]

Abstract: ABSTRACT:The variation of free-volume parameters (lifetime, intensity, and distribution) after sorption and desorption of CO 2 and CH 4 gases in the glassy polymer poly[1-(trimethylsilyl)-1-propyne] (PTMSP) and in the rubbery high-density polyethylene (HDPE) and low-density polyethylene (LDPE) were determined by the PAL technique. Size distributions deduced from PAL measurements reveal the presence of large free-volume holes in PTMSP with an average size of 0.725 nm 3 and intensity of 22% in addition to a free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…The effect of the scCO 2 treatment of the PTMSP films on the o -Ps lifetimes τ 3 and τ 4 is shown in Figure . Treating the films with pressurized CO 2 clearly induces an increase of the initial free volume, as reported for other polymers. ,,, For the present PTMSP system, both lifetimes τ 3 and τ 4 significantly increase compared to the untreated reference sample. For the scCO 2 -treated samples in the temperature range of 40−110 °C, increasing the treatment pressure has no significant effect on τ 3 and τ 4 .…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…The effect of the scCO 2 treatment of the PTMSP films on the o -Ps lifetimes τ 3 and τ 4 is shown in Figure . Treating the films with pressurized CO 2 clearly induces an increase of the initial free volume, as reported for other polymers. ,,, For the present PTMSP system, both lifetimes τ 3 and τ 4 significantly increase compared to the untreated reference sample. For the scCO 2 -treated samples in the temperature range of 40−110 °C, increasing the treatment pressure has no significant effect on τ 3 and τ 4 .…”
Section: Resultssupporting
confidence: 82%
“…These values are much larger than those reported in the literature for a similar PTMSP system treated in a CO 2 atmosphere at mild conditions. Mohsen et al observed a 7.4% increase of both lifetimes τ 3 and τ 4 for PTMSP after desorption of CO 2 at 1 bar and room temperature, thus demonstrating the large effect of pressure and temperature on the free volume expansion of scCO 2 -treated PTMSP. For other polymers like poly(ethylene naphthalate) and syndiotactic polystyrene, o -Ps lifetime increases up to ∼10% were reported after scCO 2 treatments of 6 h at 20 MPa and 100 °C and 3−10 h at 16 MPa and 40 °C, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations